Dynamic computed tomography appearance of tumor response after stereotactic body radiation therapy for hepatocellular carcinoma: How should we evaluate treatment effects?. Issue 7 (29th January 2013) - Kimura, Tomoki; Takahashi, Shigeo; Kenjo, Masahiro; Nishibuchi, Ikuno; Takahashi, Ippei; Takeuchi, Yuki; Doi, Yoshiko; Kaneyasu, Yuko; Murakami, Yuji; Honda, Yoji; Aikata, Hiroshi; Chayama, Kazuaki; et al.
<x xml:space="preserve">Abstract</x> Aim To evaluate the dynamic computed tomography (CT) appearance of tumor response after stereotactic body radiation therapy (SBRT) for hepatocellular carcinoma (HCC) and reconsider response evaluation criteria for SBRT that determine treatment outcomes. Methods Fifty‐nine patients with 67 tumors were included in the study. Of these, 56 patients with 63 tumors underwent transarterial chemoembolization using lipiodol prior to SBRT that was performed using a 3‐D conformal method (median, 48 Gy/four fractions). Dynamic CT scans were performed in four phases, and tumor response was evaluated by comparing tumor appearance on CT prior SBRT and at least 6 months after SBRT. The median follow‐up time was 12 months. Results The dynamic CT appearance of tumor response was classified into the following: type 1, continuous lipiodol accumulation without early arterial enhancement (26 lesions, 38.8%); type 2, residual early arterial enhancement within 3 months after SBRT (17 lesions, 25.3%); type 3, residual early arterial enhancement more than 3 months after SBRT (19 lesions, 28.4%); and type 4, shrinking low‐density area without early arterial enhancement (five lesions, 7.5%). Only two tumors with residual early arterial enhancement did not demonstrate remission more than 6 months after SBRT. Conclusion The dynamic CT appearance after SBRT for HCC was classified into four types. Residual early arterial enhancement disappeared within 6 months in most type 3 cases; therefore, early assessment within 3 months may result in a misleading response evaluation.